2019
DOI: 10.5812/archcid.86569
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Strongyloides sp. Infection in Diabetic Patients in the Central Part of Mazandaran, Northern Iran

Abstract: Background: Strongyloides stercoralis, a soil transmitted helminth, is well known as a potentially fatal parasite in immunosuppressed patients. Objectives: The current study aimed to evaluate the prevalence of strongyloidiasis in diabetic patients, in the central parts of Mazandaran province, Iran, using coprological examination and enzyme-linked immunosorbent assay (ELISA). Methods: Fresh stool and serum samples were obtained from diabetic patients. The stool samples were examined using direct smear and forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…This seroprevalence rate is slightly higher than previous studies in the north of Iran among the high-risk population. Previous studies reported the seroprevalence rates of strongyloidiasis as 25.6%, 27.9% and 30% in diabetic patients, suspected patients to infectious diseases and immunocompromised patients, respectively (Gorgani-Firouzjaee et al, 2018; Javanian et al, 2019;Kalantari et al, 2019). While the seroprevalence rate reported in our study is much higher than previous reports in Khuzestan Province, south-west of Iran, where the seroprevalence rates were 8.7% and 14.4% among high-risk patients (Rafiei et al, 2016;Ashiri et al, 2021).…”
Section: Discussioncontrasting
confidence: 68%
“…This seroprevalence rate is slightly higher than previous studies in the north of Iran among the high-risk population. Previous studies reported the seroprevalence rates of strongyloidiasis as 25.6%, 27.9% and 30% in diabetic patients, suspected patients to infectious diseases and immunocompromised patients, respectively (Gorgani-Firouzjaee et al, 2018; Javanian et al, 2019;Kalantari et al, 2019). While the seroprevalence rate reported in our study is much higher than previous reports in Khuzestan Province, south-west of Iran, where the seroprevalence rates were 8.7% and 14.4% among high-risk patients (Rafiei et al, 2016;Ashiri et al, 2021).…”
Section: Discussioncontrasting
confidence: 68%
“…In total, 29 studies compared baseline measures of diabetes or pancreatic inflammation in those with and without helminth infection. Seventeen studies (59%; 11 animal, 6 human) reported lower measures of diabetes or pancreatic inflammation [14,25,32,68,[72][73][74][75][76][77][78][79][80][81][82][83][84], 6 (21%; all human) demonstrated higher measures of these factors [6,[85][86][87][88][89], and 5 (17%; all human) showed no association with respect to helminth infections [53,58,59,71,90]. In the final study there was no difference in hemoglobin A1c or fasting glucose regardless of helminth infection or antiretroviral status among HIV-infected individuals, while among HIV-uninfected individuals, soil-transmitted helminth (STH) infection was inversely associated with hemoglobin A1c (5.2% vs. 5.5% in STH-uninfected controls) after adjustment for age and sex [69].…”
Section: Helminths and Diabetesmentioning
confidence: 99%
“…Of the 5 that reported on the effects of anthelmintic treatment, 3 (60%) showed that blood glucose increased after treatment of helminth infection. Among human studies that reported median age and sex distribution, 2 out of 5 [6,25,53,89,90] with median ages over 50 years observed a different cross-sectional trend and suggested that helminth infection may possibly increase diabetes risk in older women, although the sample size of studies is admittedly limited and women were over-represented in those 2 studies, which both focused on Strongyloides [89,90].…”
Section: Helminths and Diabetesmentioning
confidence: 99%